The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1080/19490976.2015.1086057
|View full text |Cite
|
Sign up to set email alerts
|

The colonic mucus protection depends on the microbiota

Abstract: The intestinal mucus is a pivotal part of our intestinal protection. It provides slow diffusion of protective molecules, trapping of luminal material as bacteria and smooth transport in the small intestine. In colon it restricts bacterial access to the epithelium limiting the responses to the enormous bacterial load present at this location. The development of these systems depends on the microbiota composition as seen in our recent study comparing the mucus phenotype in 2 colonies kept in different husbandrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 35 publications
7
33
0
Order By: Relevance
“…From our analysis of microbiome and metabolome, we could propose some ways through which bacteria affect kidney damage. For instance, it was shown that bacteria play a "nephroprotective" role (Prevotella copri [43], Faecalibacterium prausnitzii [44,45], and Coprococcus eutactus [46]), being reversely associated with the severity of AKI, and are known to produce short-chain fatty acids (SCFAs), mainly represented by acetate, propionate, and butyrate [47]. Most of these molecules (especially butyrate) are used by the intestine epithelium as an energy source, however, a fraction of these goes into the bloodstream, and then transfer to the organs, inhibiting the histone deacetylase activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…From our analysis of microbiome and metabolome, we could propose some ways through which bacteria affect kidney damage. For instance, it was shown that bacteria play a "nephroprotective" role (Prevotella copri [43], Faecalibacterium prausnitzii [44,45], and Coprococcus eutactus [46]), being reversely associated with the severity of AKI, and are known to produce short-chain fatty acids (SCFAs), mainly represented by acetate, propionate, and butyrate [47]. Most of these molecules (especially butyrate) are used by the intestine epithelium as an energy source, however, a fraction of these goes into the bloodstream, and then transfer to the organs, inhibiting the histone deacetylase activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, we identified 222 proteins, of which 58 proteins were downregulated and 75 proteins were upregulated in DSSWOL compared to the DSS group (Supplementary Table 3). WOL supplementation decreased the levels of proteins that are known to be commonly upregulated in IBD patients: calreticulin (Calr) 33 , serotransferrin (Trfe) 34 , annexin A5 (Anxa5) 35 , beta-enolase (Enob) 36 , transthyretin (Tthy) 37 , selenium-binding protein 1 (Sbp1) 38 , and protein-glutamine gamma-glutamyltransferase 2 (Tgm2) 39 ; proteins involved in fibrosis: fibrinogen beta chain (Fibb) and fibrinogen gamma chain (Fibg) 40 ; and inflammation-related proteins: histone H4 (H4), superoxide dismutase [Cu-Zn] (Sodc) 41 , cystatin-B (Cytb) 42 , 10-kDa heat shock protein, mitochondrial (Ch10) 43 , thioredoxin (Thio) 44 , and alpha-enolase (Enoa) 45 .…”
Section: Comparative Hepatic and Colonic Proteomics Analysis By Itraqmentioning
confidence: 99%
“…Consistently, while several reports support a causal relevance for Akkermansia in improving metabolic phenotypes 2,26,35,36 , molecules of microbial origin were shown to stimulate mucus release 37 and the composition of the gut microbiota plays a key role in the development of an impenetrable mucus layer. 38 In addition, Akkermansia has been shown to fortify in vitro the integrity of the epithelial cell layer, suggesting that the positive role of this bacterium in the gut barrier is not exclusively associated with mucus layer physiology. 39 An important question is whether administration of Akkermansia should be regarded as a safe approach to prevent or even reverse metabolic diseases.…”
Section: Is Akkermansia a New Bacterial Weapon To Fight Chronic Inflamentioning
confidence: 99%